(untitled) (Ozone Therapy Global Journal, 2012)
The good results referred by many authors in the treatment of degenerative diseases: Arthritis and Chondromalacia in the knee. Also in acute pathologies: fractures where speeds up time building bone, or muscles and tendons injuries prompted team Gabinet Médic Maresme (Mataró, Spain) to the application of Plasma Rich in Protein for treatment in the vertebral column making mixed therapy with the placement of the intervertebral disk with subacute or chronic injury of protrusion or herniated disk (excluding extruded herniation) and, at the same time, to administer the Poor Plasma Protein in posterior facet joint affected of overload or declared arthrosis clamping. The technique is done in surgery room, under sedation ambulatory medical control of anesthetic, with radioscopic C-arm image intensifier with high definition. Previously we apply ozone both fractions of plasma to their implementation in a closed circuit, strict rules of asepsis, with antibiotic-therapy (2 grams of Cefazolin as prophylactic dose) It is this preliminary report on 50 clinical cases, both involving the lumbar spine as the cervical (december 2010-agost 2011). Our results: -Regenerative potentiality of the PRPO3 with early analgesic effect. -Regenerative capacity of posterior joints thanks to the double effect PPP more ozone. -Antiseptic effect of ozone on the disk and neighbor structures. -Technique ambulatory and minimally invasive with few risks. -Leave completely open to the possibility other treatments or more applications in consultation- room to the ideal point of clinical and functional outcome. -Satisfactory results in 85% of cases.